2017
DOI: 10.3892/ol.2017.7334
|View full text |Cite
|
Sign up to set email alerts
|

Targeted sequencing of cancer‑associated genes in hepatocellular carcinoma using next‑generation sequencing

Abstract: Abstract. Hepatocellular carcinoma (HCC) is the third leading cause of cancer mortality worldwide. Although the clinical success rate for the treatment of early-stage HCC has improved, the prognosis of advanced HCC remains poor owing to the high recurrence rate and the refractory nature of HCC for various anticancer drugs. A better understanding of the pathogenesis of HCC is therefore critically needed in order to treat HCC, including its genetic alterations. Next-generation sequencing (NGS) has provided an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The TP53 mutations in tumors at advanced stages were significantly more frequent when compared with those in early-stage tumors. The results of the present study offer new insights and improved understanding of the etiology and the development of HCC [ 40 ]. Table 1 summarizes other studies related to p53 mutations and the use of NGS technique.…”
Section: Role Of P53 In Human Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…The TP53 mutations in tumors at advanced stages were significantly more frequent when compared with those in early-stage tumors. The results of the present study offer new insights and improved understanding of the etiology and the development of HCC [ 40 ]. Table 1 summarizes other studies related to p53 mutations and the use of NGS technique.…”
Section: Role Of P53 In Human Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…Thus, detected C>G transversion could be a good indicator of immunotherapy efficacy. In spite of high C>G transversion being found in HCC and believed as an etiology of HCC by Morishita et al ( 30 ), they did not associate it with any biological significance. Our results revealed that patients with high C>G transversion were strongly associated with poorly differentiated HCC, involving in APOBEC-related mutagenesis.…”
Section: Discussionmentioning
confidence: 87%
“…Primers were designed for amplicon sequencing of 147 loci used in the 2021 SNV comparison test run by the International Society for Animal Genetics (ISAG) [ 34 , 35 ]. These primers were included in the panel for the gene-editing test, and library preparation and sequencing by NGS were performed simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…NGS technology has enabled large-scale whole-genome resequencing (WGR), whole-exome resequencing (WER), and targeted gene or exon resequencing of species with reference genome sequences. WGR and WER are generally used to search for mutations causative of hereditary diseases [ 32 , 33 ], and targeted resequencing is often used to detect mutations in genes associated with cancer [ 34 ].…”
Section: Introductionmentioning
confidence: 99%